BRAF V600E mutation and the Bethesda System for Reporting Thyroid Cytopathology of fine-needle aspiration biopsy for distinguishing benign from malignant thyroid nodules. Issue 37 (17th September 2021) - Sheng, Danli; Yu, Xiaoli; Li, Hui; Zhang, Murui; Chen, Jianzhong
Abstract: Background: The Bethesda System for Reporting Thyroid Cytopathology (TBSRTC) predicts the risk of malignancy for the different categories of the ultrasound-guided fine-needle aspiration biopsy (FNAB). The objective of this study is to investigate the efficiencies of the v-raf murine sarcoma viral oncogene homolog B1 ( BRAF ) V600E mutation test and the TBSRTC categories in distinguishing between benign and malignant thyroid nodules. Methods: In this study, 362 ultrasound-guided fine-needle aspiration (FNA) samples from 344 patients aged from 17 to 76 years old were retrospectively reviewed. The patients were classified into six groups (I–VI) according to the TBSRTC system. The amplification refractory mutation system-polymerase chain reaction (ARMS-PCR) was used to evaluate the BRAF V600E mutation level in total 362 samples. Among of the 344 patients, 128 patients (131 thyroid nodules) who underwent surgeries were followed by histopathological examination. The predictive values of the BRAF V600E mutation test and TBSRTC categories were evaluated in these 131 thyroid nodules. Results: The median ages of the patients in the TBSRTC IV–VI group were smaller than those in the TBSRTC I–III groups. The proportion of nodules over 1 cm was larger than it in the TBSRTC IV group compared to the other groups. Significant differences in BRAF V600E mutation were observed ( P < .001) among these six groups. The sensitivity (89.57%) for the detection of malignant thyroid nodules, negative predictive value (NPV; 45.45%) for the detection of benign nodules, and accuracy (86.26%) for distinguishing between benign and malignant thyroid nodules increased by combining the BRAF V600E mutation test and TBSRTC system when compared with the BRAF V600E mutation test and TBSRTC system respectively. The BRAF V600E mutation test alone demonstrated the increased positive predictive value (PPV; 98.91%) and specificity (93.75%) for the detection of malignant thyroid nodules compared to the TBSRTC method (alone or in combination with the BRAF V600E method). Conclusion: In summary, significant differences in age, nodule diameter, and BRAF V600E mutation were noted among the six categories of the TBSRTC system. The combination of the BRAF V600E mutation test and TBSRTC system demonstrated increases in the NPV, sensitivity, and accuracy, while the BRAF V600E method proved superiority to the TBSRTC system with regard to the PPV and specificity.